Schweiz ohne Armee - [Friedenstaube mit Ölzweig in blühendem Baum]
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Friedensbewegung politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Pazifismus Sicherheitspolitik;Verteidigung;Armee;Armeeabschaffung;GSoA